(untitled) (Altre Modernità, 2024)
Nobody in the Wilderness: A Mental Health Record of a Patient with Depression (2008) is the first of a number of memoirs that contemporary Chinese writer Li Lanni (1956- ) has composed to document her fight against the depression that hit her in 2003, after being cured of thyroid cancer. The memoir brings together Li’s diary entries from different moments of her life, excerpts from her (semi-)autobiographical literary production since the 1980s, memories of life during the Cultural Revolution, medical reports, extracts from scientific studies of mental illness, Bible citations, accounts of the SARS (severe acute respiratory syndrome) epidemic, and much more. This stratified narrative, where different genres, discourses, and temporalities intersect, encourages a new reflection on depression, its embodiment, and its meanings. Drawing on literary and medical anthropological understandings of embodiment and illness, this article examines Li Lanni’s articulation of depression to shed light on the potential of writing to destigmatize depression and legitimize her particular embodiment of illness against objectifying biomedical and socio-cultural discourses. The analysis of the narrativization of depression as a “montage” of heterogeneous elements and of the reconfiguration of illness as “hereditary”—at once bound to personal, familial, and collective experiences—illuminates the multiple ways in which the memoir complicates body/mind dichotomies and notions of responsibility in contexts of illness. Ultimately, bearing witness to suffering that transcends Li’s own suffering, the memoir acquires an ethical dimension that rests on the ambiguous relationship between the personal and the collective.